Study of MnO₂/Ni-MCM-41 Catalyst for CO Oxidation in Motorcycle Exhaust Emissions - Alvin Romadhoni Putra Hidayat; Alvin Rahmad Widyanto; Ratna Ediati; Hafildatur Rosyidah; Romario Abdullah (Universitas Diponegoro, 2026)
Incomplete combustion in vehicles produces hazardous gases such as carbon monoxide (CO), which is harmful to human health. This study aimed to synthesize MnO₂/Ni-MCM-41 as a catalyst for CO oxidation to CO₂. MCM-41 was synthesized via a hydrothermal method, followed by Ni doping to form Ni-MCM-41 and subsequent wet impregnation to obtain MnO₂/Ni-MCM-41. The materials were characterized by FTIR, XRD, TEM, and N₂ physisorption, while catalytic activity for CO oxidation was evaluated using a four-stroke motorcycle. FTIR spectra showed a band at 1633.76 cm⁻¹ attributed to –OH vibrations corresponding to Si–OH groups in MCM-41, whereas XRD patterns exhibited characteristic peaks at 2θ = 2.5° for MCM-41 and 2θ = 25° for δ-MnO₂. TEM analysis confirmed the hexagonal mesostructure of MCM-41, consistent with previous reports, while N₂ physisorption revealed a type IV isotherm, indicating a mesoporous structure. Ni incorporation decreased the specific surface area but enhanced the number of active sites. Increasing reaction time reduced CO concentration, while CO₂ concentration increased correspondingly. The optimum catalytic performance was obtained for MnO₂/Ni-MCM-41 with an impregnation time of 10 h.